Analysis of Accounting Information System in Sales Decision Making in PT. Nusantara IV Adolina Tebing Tinggi - Riang Gembira Tampubolon; Junawan; Puja Rizqi Ramadhan (Britain International for Academic Research (BIAR-Publisher), 2022)
This study aims to examine and determine the sales information system in decision making sales applied by PT. Nusantara IV Adolina Plantation. The sample in this study was the procedures and criteria for sales accounting information system and decision making sales at PT. Nusantara IV Plantation Adolina North Sumatra. Data was collected by observation and interview methods. The analysis was conducted with qualitative and quantitative methods. Bay comparing theory with actual practice occurred, as well as the testing of the relevant documents. In the sales system, part of marketing and procrument functions accept mail orders from byers, edit orders from customers to add any missing information in the letter of the order, request credit anuthorization, specify the delivery date and of the warchouse where the goods will be shipped and fill mail order delivery as the winning bidder. Based on the analysis conducted, PT. plantation Nusantara IV Adolina transparency and validity of the data presented must meet the standards that exist, so trustworthy and can be used by the marketing as a support and decisions making. Thus PT Plantation Nusantara IV Adolina is able to earn profits as well as expand the market and increase greater sales.